Radość polityki - Koczanowicz, Leszek (Fabrica Litterarum Polono-Italica, 2024)
The article deals with a problem that is neglected in reflection on politics, namely whether politics, doing politics, can be a source of joy. Various positions on the matter are considered, from ancient writings to modern newspapers or even tabloids. The constraints on active politicians and the concerns that their private lives may raise are shown. The second theme of the article is the enjoyment of politics by citizens who are not professional politicians. Can participating in democracy, in democratic procedures, be something joyful for them? The thesis of the article is that this is generally not the case, that negative emotions dominate in politics, including democratic politics. The article concludes with the postulate that for a democratic society to function well, it is necessary to restore the joy of participating in democracy.